Evidence for proton shuffling in a thioredoxin-like protein during catalysis. - Narzi, Daniele; Siu, Shirley Weng In; Stirnimann, Christian U.; Grimshaw, John P. A.; Glockshuber, Rudi; Capitani, Guido; Böckmann, Rainer (Journal of Molecular Biology, 2008)
Proteins of the thioredoxin (Trx) superfamily catalyze disulfide-bond formation, reduction and isomerization in substrate proteins both in prokaryotic and in eukaryotic cells. All members of the Trx family with thiol-disulfide oxidoreductase activity contain the characteristic Cys-X-X-Cys motif in their active site. Here, using Poisson-Boltzmann-based protonation-state calculations based on 100-ns molecular dynamics simulations, we investigate the catalytic mechanism of DsbL, the most oxidizing Trx-like protein known to date. We observed several correlated transitions in the protonation states of the buried active-site cysteine and a neighboring lysine coupled to the exposure of the active-site thiolate. These results support the view of an internal proton shuffling mechanism during oxidation crucial for the uptake of two electrons from the substrate protein. Intramolecular disulfide-bond formation is probably steered by the conformational switch facilitating interaction with the active-site thiolate. A consistent catalytic mechanism for DsbL, probably conferrable to other proteins of the same class, is presented. Our results suggest a functional role of hydration entropy of active-site groups.